ETIKA SEKSUALITAS DALAM RUMAH TANGGA - Rimanto, Rimanto; Hermanto, Agus; Yuhani'ah, Rohmi (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2025)
Psychologically, men in marriage are active in biological needs, while women tend to be more passive and are more likely to seek affection and protection. Conflicts that occur in marriage are often caused by the unmet needs of both parties. The question is how urgent are biological needs in a marriage? This study aims to uncover the importance of awareness among both husband and wife in fulfilling each other's rights, particularly in the context of sexual relations. This is qualitative research in the form of a literature review that examines the importance of biological relations in marriage from the perspectives of religious scholars and medical professionals, then analyzes it from an Islamic perspective to form a sexual ethics within the family. This study shows that biological relations are a key factor in achieving a peaceful family (sakinah), where the true meaning of marriage is to make the relationship between husband and wife lawful in fulfilling biological needs, which is tied to a legitimate marriage bond, resulting in legal and quality offspring